PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR DAN SIKAP ILMIAH SISWA PADA MATERI KEANEKARAGAMAN HAYATI DI KELAS X MAN 1 PONTIANAK - Purwaningsih, Eny; Ariyati, Eka Ariyati; Ganda Putri Panjaitan, Ruqiah (Universitas Tanjungpura, 2014)
This research was aimed to determine the implementation of cooperative learning through two stay two stray type toward the students achievement and behavior on biodiversity material on tenth grade students in MAN 1 Pontianak. Quasi experiment by control group pre-test post-test design was used as the form of research. The tools of data collecting were students test result in essay and questionnaires. The students average score of post-test by using two stay two stray learning method is 28,27 meanwhile the students behaviour average is 73,74 %. It showed that the implementation of two stay two stray can increase students learning achievement and behaviour.Keywords: two stay two stray, biodiversity.